Teacher education policy to improve teacher quality: Substantive reform or just another hurdle?. Issue 3 (18th May 2020) - Barnes, Melissa; Cross, Russell
ABSTRACT: Mounting criticism suggests that the recent introduction of a 'gatekeeping' test to improve the quality of teachers in Australia—the Literacy and Numeracy Test for Initial Teacher Education (LANTITE)—has had limited success in achieving its aim. Shaped by a discourse of inputs on how teacher quality might be achieved ('quality in, quality out'), LANTITE was to address the apparent decline in the quality of Australian teachers by reforming how candidates were being admitted into initial teacher education courses. This paper presents a quantitative analysis of 2, 013 LANTITE scores, alongside the qualitative perspectives of 109 final year teacher candidates, to argue that LANTITE does little to change who gains admission into initial teacher education but is instead an ineffective mechanism for improving quality and a costly hurdle for candidates.